A Specifically Designed Injector for Controlled Lube Oil Addition in View of Investigation of Pre-Ignition Phenomena in Dual–Fuel/Gas Engines - Süess, Pascal; Schneider, Bruno; Wüthrich, Dario; Wüthrich, Silas; Herrmann, Kai (Frontiers in Mechanical Engineering, 2021)
Internal combustion engines will continue to play a role during a transitional phase, especially in heavy-duty or marine applications. In this context, lean-burn gas/dual-fuel combustion is an attractive concept to reduce CO2, combined with considerably lower particulate and NOX pollution, and with efficiencies comparable to diesel combustion. However, ignition processes still pose considerable challenges, with pre-ignition in particular being a major issue. The underlying mechanisms are probably based on self-ignition of lube oil in hot zones. In order to investigate fundamentals of such phenomena in optically accessible test rigs, a novel injector was specifically developed to induce pre-ignitions artificially. The so-called "PieZo-Droplet-Injector" (PZDI) enables dosing of minor amounts of lubricating oil or even the injection of single droplets with diameters in the range of 100 to 200 µm. The working principle relies on a needle actuated with a piezo stack, which pushes a certain amount of lube oil in a bore so that (even single) droplets can be ejected through an adjustable nozzle. To confirm the PZDI functionality and to investigate droplet characteristics based on adjustable operating parameters, tests were performed under ambient conditions as well as in a constant volume combustion chamber under reasonable pressure and temperature conditions. Overall, the PZDI showed an excellent behavior in terms of capabilities to inject small amounts or even single droplets of lube oil. At last, this specially developed injector allows selective lube oil addition in an optically accessible engine test facility for upcoming examination of pre-ignition phenomena under real operating conditions.